Social and psychological impact of sexual harassment victims: a literature review - Zulkarnain, Zulkarnain; Retno Dwiningrum, Nawang (Borneo Novelty Publishing, 2025)
This systematic literature review analyzes the social and psychological impacts experienced by victims of sexual violence, aiming to provide a comprehensive synthesis of the effects reported in recent research. This study uses a systematic literature review approach that utilizes Scopus as the main database, studies published in the last decade were selected to address social stigma, psychological disorders, and recovery challenges faced by victims. The findings of this study show the recurrent prevalence of trauma-related disorders, including depression, anxiety, and post-traumatic stress disorder (PTSD), and an important impact on social dynamics such as stigma and secondary victimization. The results of this study are very important to understand the risk of sexual violence and harassment. This research is expected to be able to be considered in order to improve the structure of social support and clinical interventions to encourage victim recovery.